Pyruvate decarboxylase and thiamine biosynthetic genes are regulated differently by Pdc2 in S. cerevisiae and C. glabrata. - Christine L Iosue; Julia M Ugras; Yakendra Bajgain; Cory A Dottor; Peyton L Stauffer; Rachael A Hopkins; Emma C Lang; Dennis D Wykoff (PLoS ONE)
Understanding metabolism in the pathogen Candida glabrata is key to identifying new targets for antifungals. The thiamine biosynthetic (THI) pathway is partially defective in C. glabrata, but the transcription factor CgPdc2 upregulates some thiamine biosynthetic and transport genes. One of these genes encodes a recently evolved thiamine pyrophosphatase (CgPMU3) that is critical for accessing external thiamine. Here, we demonstrate that CgPdc2 primarily regulates THI genes. In Saccharomyces cerevisiae, Pdc2 regulates both THI and pyruvate decarboxylase (PDC) genes, with PDC proteins being a major thiamine sink. Deletion of PDC2 is lethal in S. cerevisiae in standard growth conditions, but not in C. glabrata. We uncover cryptic cis elements in C. glabrata PDC promoters that still allow for regulation by ScPdc2, even when that regulation is not apparent in C. glabrata. C. glabrata lacks Thi2, and it is likely that inclusion of Thi2 into transcriptional regulation in S. cerevisiae allows for a more complex regulation pattern and regulation of THI and PDC genes. We present evidence that Pdc2 functions independent of Thi2 and Thi3 in both species. The C-terminal activation domain of Pdc2 is intrinsically disordered and critical for species differences. Truncation of the disordered domains leads to a gradual loss of activity. Through a series of cross species complementation assays of transcription, we suggest that there are multiple Pdc2-containing complexes, and C. glabrata appears to have the simplest requirement set for THI genes, except for CgPMU3. CgPMU3 has different cis requirements, but still requires Pdc2 and Thi3 to be upregulated by thiamine starvation. We identify the minimal region sufficient for thiamine regulation in CgTHI20, CgPMU3, and ScPDC5 promoters. Defining the cis and trans requirements for THI promoters should lead to an understanding of how to interrupt their upregulation and provide targets in metabolism for antifungals.